(untitled) (Baghdad Science Journal, 2005)
Suggested in this study the introduction of monomers have the ability to interact with polyester Rzn way confused or Alchapak Vodev polycarbonate first Almiaal acrylate ????? grains and offered models for high temperature and for a period of time of 40 days and absorbance and penetration and after color changes resulting from the storage heat higher using shades where models were extractedthermal storage and take measurements and then returned periodically results were consistent with theoretical expectations and mixing